Managing the paradox: Individual ambidexterity, paradoxical leadership and multitasking in entrepreneurs across firm life cycle stages - Klonek, Florian; Volery, Thierry; Parker, Sharon (2020)
Ambidexterity requires both exploration and exploitation. However, our understanding of the individual ambidexterity concept, its association with multitasking behaviours and paradoxical leadership across the firm life cycle of entrepreneurs remains limited. In this article, we examine 4355 behavioural activities related to exploration and exploitation from 12 entrepreneurs. We first demonstrate that entrepreneurs display self-sustaining activity cycles; that is, exploration tended to be followed by exploration and exploitation tended to be followed by exploitation. Second, when multitasking behaviours were high, entrepreneurs had lower levels of ambidextrous switching. Third, we found an association between entrepreneurial ambidexterity and paradoxical leadership; this was moderated by the firm life cycle stage. As such, this article contributes to a better understanding of individual ambidexterity, leadership and multitasking in entrepreneurs.